-6(8x+3)=-3x+27

Simple and best practice solution for -6(8x+3)=-3x+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(8x+3)=-3x+27 equation:


Simplifying
-6(8x + 3) = -3x + 27

Reorder the terms:
-6(3 + 8x) = -3x + 27
(3 * -6 + 8x * -6) = -3x + 27
(-18 + -48x) = -3x + 27

Reorder the terms:
-18 + -48x = 27 + -3x

Solving
-18 + -48x = 27 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-18 + -48x + 3x = 27 + -3x + 3x

Combine like terms: -48x + 3x = -45x
-18 + -45x = 27 + -3x + 3x

Combine like terms: -3x + 3x = 0
-18 + -45x = 27 + 0
-18 + -45x = 27

Add '18' to each side of the equation.
-18 + 18 + -45x = 27 + 18

Combine like terms: -18 + 18 = 0
0 + -45x = 27 + 18
-45x = 27 + 18

Combine like terms: 27 + 18 = 45
-45x = 45

Divide each side by '-45'.
x = -1

Simplifying
x = -1

See similar equations:

| 20+0.12h=80 | | y=(400+20x)(90+1x) | | n^2+8n=180 | | X+6=x+15 | | x(x+7)=73 | | 23-16n=-1 | | 3m2/8=6 | | -7(6x+5)=-7x+14 | | 0=00m | | 1,340,000,000,000i=23 | | -15=-1.5m | | (2x-4y+6)dx=(3-x-y)dy | | 3tan^2x+4=5 | | (6)(3i+4)(1)+(4y+1)(2i)=(8iy+2i)+(18i+24) | | 19x+13y=7 | | -8x+4y=-12 | | 15-d=8 | | 0.045x-5/8y=120 | | x^8-26x+25=0 | | 2x+14i=1 | | (x^3+3x^2-16x-48)=0 | | -37+46.98-(-0.02)= | | 5s-(100+2s)=0 | | 3(10-6)(3-7)= | | 55m-139m-64m= | | 8x^6/6x^3 | | ln(x-3)=1.4 | | x-9(2/3x-6)=30 | | 1/2z=9/4 | | -5/13x=-8 | | 5m-139m-64m= | | 10m^3n^3-2mn^2+14mn= |

Equations solver categories